GENETIC ANALYSIS OF SUPEROXIDE DISMUTASE 1 GENE IN MURRAH RIVER BUFFALO - N. B. Stafuzza; M. M. Borges; M. E. J. Amaral-Trusty (Journal of Animal and Plant Sciences, 2014)
In this study we characterized the complete sequence of the SOD1 gene from an animal representing the Murrah breed of the river buffalo (Bubalus bubalis) and we compared its coding sequence and the amino acid sequence with its homologous from others mammals. The buffalo SOD1 gene contains 8,720 bp in length organized into five exons (72 bp, 91 bp, 70 bp, 118 bp and 108 bp, respectively), four introns (3,630 bp, 1,768 bp, 827 bp and 1,614 bp, respectively), 5’UTR (103 bp) and 3’UTR (319 bp), with the exon/intron size ratio of 1:17.07 and the CG level of 46.42 %. A total of 12 repetitive elements were identified at intronic level. Comparative analysis between SOD1 gene coding sequence and the amino acid sequence with its homologous from other mammalian species showed a percentage identity varying from 82% to 98% at DNA coding level and 81% to 97% at amino acids level. In addition, the alignment of the complete SOD1 gene sequence between the Murrah and the Mediterranean breeds revealed nine potential SNPs which could be candidates for validation in commercial buffalo populations.
Keywords: BAC library; Bubalus bubalis; Murrah breed; Pyrosequencing; SOD1